KEBERKESANAN KAEDAH â€œNUMBERED HEADS TOGETHERâ€ TERHADAP PENCAPAIAN BIOLOGI DALAM KALANGAN PELAJAR DI UNIVERSITI PENDIDIKAN SULTAN IDRIS (Sains Humanika, 2010)
This study examines the effect of using â€œNumbered Heads Together,â€ a cooperative learning strategy, as compared to the lecture approach on the Biology achievement amongst undergraduates at UPSI. Employing the pretestâ€“posttest control group design with random assignment, 30 students were assigned to the cooperative learning group while another 30 students to the lecture group. Student achievement in â€œHuman Respiratory System,â€ a subtopic in the Introductory Biology II (officially coded as TBA1023) was measured using a researcherâ€“generated instrument consisted of 20 multipleâ€“choice items and that has adequate validity and reliability. Analysing the data set using Analysis of Covariance (ANCOVA), the results indicate that the adjusted mean (79.90) of the cooperative learning group is statistically significantly higher (F(1,57) = 16.63, p < .001) than the adjusted mean of the lecture group. The obtained effect size (Î” = +0.83), which is equivalent to approximately four fifth of a standard deviation, denotes the educational significance, favouring the Numbered Heads Together cooperative learning group. These findings are discussed in the context of educational practice in higher education and equally, implications for future research are proffered
Keywords: Cooperative learning; numbered heads together; biology education